Diagnostic Performance of Cardiopulmonary Exercise Testing (CPET) in Chronic Obstructive Pulmonary Disease (COPD) at a Tertiary Hospital in Indonesia - Musdalifah Musdalifah; Hendrastutik Apriningsih; A. Farih Raharjo (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2026)
Background: Chronic obstructive pulmonary disease (COPD) remains a major global health burden. Spirometry as the diagnostic gold standard, still has limitations for functional assessment. The existence of cardiopulmonary exercise testing (CPET) provides a comprehensive evaluation of integrated cardiopulmonary and metabolic responses during exercise and may improve diagnostic and management decisions in COPD. This study determined the diagnostic quality of CPET parameters for COPD. Methods: This observational analytic cross-sectional study used paired spirometry and CPET data from medical records at Universitas Sebelas Maret Hospital. Thirty-seven eligible records were analyzed after obtaining ethics approval. CPET parameters included maximal oxygen uptake (VO2max), respiratory exchange ratio (RER), and the slope of the ratio between minute ventilation volume and carbon dioxide production volume (VE/VCO2 slope). Discrimination was assessed using AUC, diagnostic performance was assessed using the chi-square test, and correlation with obstruction severity was assessed using the GOLD classification, with a value of P<0.05 being significant. Results: Of 37 subjects, 62.2% had COPD. COPD status was significantly associated with older age and smoking (both P<0.05). VO2max (sensitivity 73.9%; specificity 78.6%; AUC=0.795; P=0.002), RER (sensitivity 78.3%; specificity 78.6%; AUC=0.846; P=0.001), and VE/VCO2 slope (sensitivity 78.3%; specificity 71.4%; AUC=742; P=0.003) showed useful discrimination. Among CPET parameters, RER correlated significantly with obstruction severity by GOLD (P<0.05), while VO2max and VE/VCO2 slope did not (P>0.05), though trends were worse with more severe disease. Conclusion: The integration of CPET with spirometry provides a more comprehensive approach to the diagnosis and management of COPD.